LIBERALISM IN CRISIS: PERSPECTIVES FROM ARTS AND HUMANITIES - Buragohain, Aloy (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper is a study of the liberal global order and its strategies to thwart the ideological challenge posed to it by the disorderly body. It begins with an exploration of the body as the primary subject of the performing arts. Following an elucidation of the emancipatory potential of the body, the paper undertakes a critical survey of liberalism and its successive ideological waves, each of which arose in response to crises in the preceding wave. In the aftermath of the economic downturn of 2008 and the resultant crisis in neoliberalism, behavioural economics emerged as the go-to policy paradigm for neoliberal policymakers. This discipline, the paper goes on to show, subordinates human agency to the structural environment, besides facilitating reproduction and reinforcement of the neoliberal ideology. Behavioural interventions like nudges operate within the political philosophy of libertarian paternalism, which is identified as a strategic tool to rationalize and order the irrational or disorderly body. This historical process is interpreted as a project to appropriate this subversive body in the service of the same structures that it could potentially subvert.